The Study of Qiyas as a Legal Argument: Application and Limitations - Azmi, Ammar Muhammad Jundy; Avicena, Fayiz Yan (Global Research Network, 2024)
This article aims to describe the position of qiyas in Islamic law. From this literature-based study, it is known that the fourth source of law, after the Qur’an, Sunnah, and ijma' (consensus), is qiyas. It is an essential tool for exploring the texts of the Qur’an and Sunnah (primary sources of Islamic law) that can be used to determine the legal basis for issues not explicitly addressed in the texts. By employing qiyas, various problems that cannot be resolved by the Qur’an, Sunnah, or ijma' can ultimately be addressed with solutions beneficial to society. Therefore, claiming that qiyas is merely a restrictive theory is incorrect. This is because most of the rules contained in the primary sources of Islamic law, particularly the Qur’an, are broad and global in scope. Since qiyas is an interpretation of the first two sources of law, it has a speculative (dzanni) nature. Consequently, there is a possibility of significant differences of opinion among Muslim scholars.